Dolphin-assisted cast net fishery in the Ashtamudi Estuary, south-west coast of India - Biju Kumar, A.; Smrithy, R.; Sathasivam, K. (Indian Journal of Fisheries, 2012)
This paper documents the traditional cast net fishery prevailing in the Ashtamudi Estuary situated along the south-west coast of India, taking advantage of the behavioural patterns of Indo-Pacific humpback dolphin, Sousa chinensis (Osbeck, 1765). The feeding-related behaviours noted were sudden rush towards the prey with shuttling or speedy zigzagging backwards and forwards and fish-stunning by tossing them into the air. The artisanal fishermen cast their nets in front of the advancing dolphins and the primary prey of dolphins in Ashtamudi Estuary was recorded as mullets. In general, the total catch recorded in the dolphin assisted cast net fishery (DAF) was significantly higher than fishery without them. The principal threat to dolphins in the Ashtamudi Estuary is the heavy traffic of trawlers and other motorised fishing vessels. The first reported Indian case of DAF is ‘parasitic’ as the benefit primarily remains with the fishermen.